Red pigments in autumn leaves of Norway maple do not offer significant photoprotection but coincide with stress symptoms - Mattila Heta; Tyystjärvi Esa (OXFORD UNIV PRESS, 2025)
The reasons behind autumn colors, a striking manifestation of anthocyanin synthesis in plants, are poorly understood. Usually, not all leaves of an anthocyanic plant turn red or only a part of the leaf blade turns red. In the present study, we compared green, red and yellow sections of senescing Norway maple leaves, asking if red pigments offer photoprotection, and if so, whether the protection benefits the senescing tree. Green and senescing maple leaves were illuminated with strong white, green or red light in the absence or presence of lincomycin which blocks photosystem II (PSII) repair. Irrespective of the presence of anthocyanins, senescing leaves showed weaker capacity to repair PSII than green leaves. Furthermore, the rate of photoinhibition of PSII did not significantly differ between red and yellow sections of senescing maple leaves. We also followed pigment contents and photosynthetic reactions in individual leaves, from the end of summer until abscission of the leaf. In maple, red pigments accumulated only during late senescence, but light reactions stayed active until most of the chlorophyll had been degraded. PSII activity was found to be lower and non-photochemical quenching higher in red leaf sections, compared with yellow sections of senescing leaves. Red leaf sections were also thicker. We suggest that the primary function of anthocyanin synthesis is not to protect senescing leaves from excess light but to dispose of carbohydrates. This would relieve photosynthetic control, allowing the light reactions to produce energy for nutrient translocation at the last phase of autumn senescence when carbon skeletons are no longer needed.